Efektivitas Model Pembelajaran Inquiry terhadap Kemampuan Berpikir Kreatif Siswa pada Materi Teorema Pythagoras - Nelpita Ulandari; Rahmi Putri; Febria Ningsih; Aan Putra (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
By the theory, the inquiry learning model can improve the students' mathematical creative thinking skills due to the students learn by themselves intensively, involved in the learning process directly and they can find and investigate any problems logically and systematically. This study aims to find out the inquiry learning process in the Pythagorean Theorem topic and its effectiveness to increase the sudents’ mathematical creative thinking skills. This research used the mixed method with sequential exploratory model. The population of this research is the VIII students of the state islamic junior high school (MTsN) 6 Kerinci. The VIII C and the VIII A of MTsN 6 Kerinci were selected as the experimental and the control group through random sampling technique. The data of learning process was obtained through observation and the data of students' mathematical creative thinking skills was obtained through the tests of mathematical creative thinking skills. The results of data analysis concluded that the inquiry learning model was effective to improve the students’ mathematical creative thinking skills.